The possibilities of improving reproductive performance by using progestogen and different doses of PMSG in Akkaraman ewes during the normal breeding season - Yilmaz, O; Denk, H; Arslan, M (Indian Veterinary Journal, 2003)
[Abstract Not Available]
Keywords: Estrus Synchronization; Anestrous Ewes; Induction; Sheep; Fertility; Sponges